Toxicity of formalin, malachite green, and the mixture to four life stages of rainbow trout - Bills, T. D. (My University, 1974)
Formalin, malachite green, or a mixture of them are utilized in fish culture for control of external parasites of fish and control of fungus on fish and fish eggs. Very little information is available concerning the toxicity of these compounds to fish under laboratory test conditions or the differences in sensitivity to these chemicals at various life stages. This study was designed to 1) determine the toxicity of formalin, malachite green and the mixture to four life stages of rainbow trout (Salmo gairdneri) under various laboratory test conditions, 2) determine the degradation of formalin and malachite green in water, 3) determine the effect of additive toxicity, and 4) determine the differences in sensitivity of two different lots of eggs to the chemicals. The 96-hour LC50 (lethal concentration required to produce 50% mortality) for formalin against rainbow trout in soft water ranged from 580 micrograms/liter for the eyed egg stage to 134 micrograms/liter for the fingerling stage. The 96-hour LC50 for malachite green against rainbow trout in soft water ranged from 2.00 mg/L for the eyed egg stage to 0.0224 mg/L for the fingerling stage. The additive indices for formalin and malachite green when applied in combination show strictly additive toxicity as the ranges overlap zero in all tests. Deactivation indices for formalin and malachite green show essentially no change in toxicity of the solutions to rainbow trout when aged for periods of 1, 2, and 3 weeks.
Keywords: Fungicides -- Toxicology; Malachite -- Toxicology; Formaldehyde -- Toxicology; Rainbow trout